Symmetric waterbomb origami - Chen, Y; Feng, H; Ma, J; Peng, R; You, Z (Royal Society, 2016)
The traditional waterbomb origami, produced from a pattern consisting of a series of vertices where six creases meet, is one of the most widely utilised origami patterns. From rigid origami viewpoint, it generally has multiple degrees of freedom, but when the pattern is folded symmetrically, the mobility reduces to one. This paper presents a thorough kinematic investigation on symmetric folding of the waterbomb pattern. It has been found that the pattern can have two folding paths under certain circumstance. Moreover, the pattern can be used to fold thick panels. Not only do the additional constraints imposed to fold the thick panels lead to single degree of freedom folding, but the folding process is kinematically equivalent to the origami of zero-thickness sheets. The findings pave the way for the pattern being readily used to fold deployable structures ranging from flat roofs to large solar panels.